2020
DOI: 10.5551/jat.52100
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Prevents Diabetes-Induced Vascular Dysfunction in ApoE-Deficient Mice

Abstract: Recent studies have demonstrated that selective sodium-glucose cotransporter 2 inhibitors (SGLT2is) reduce cardiovascular events, although their mechanism remains obscure. We examined the effect of canagliflozin, an SGLT2i, on atherogenesis and investigated its underlying mechanism. Method: Canagliflozin (30 mg/kg/day) was administered by gavage to streptozotocin-induced diabetic apolipoprotein E-deficient (ApoE /) mice. Sudan IV staining was performed at the aortic arch. Immunostaining, quantitative RT-PCR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 43 publications
3
34
0
1
Order By: Relevance
“… 59 The weight loss occurs rapidly at first and then slows down until it reaches a plateau. 60 , 61 , 62 The initial rapid loss is considered to be the result of osmotic diuresis, while the subsequent slow loss may be the result of urinary glucose excretion causing a decrease in visceral fat mass. 63 , 64 There is evidence that obesity is an important risk factor for heart failure, but it is still controversial whether weight loss affects the outcome of patients with diabetes with significant heart failure.…”
Section: Possible Mechanisms Of Cardiovascular Benefitsmentioning
confidence: 99%
“… 59 The weight loss occurs rapidly at first and then slows down until it reaches a plateau. 60 , 61 , 62 The initial rapid loss is considered to be the result of osmotic diuresis, while the subsequent slow loss may be the result of urinary glucose excretion causing a decrease in visceral fat mass. 63 , 64 There is evidence that obesity is an important risk factor for heart failure, but it is still controversial whether weight loss affects the outcome of patients with diabetes with significant heart failure.…”
Section: Possible Mechanisms Of Cardiovascular Benefitsmentioning
confidence: 99%
“…The duration of our experiment was 12 weeks, and the experimental group was treated with SGLT2 inhibitors since the 7th week. Combining previous studies, we found that SGLT2 inhibitors may inhibit in ammatory mediators with a duration of at least 8 weeks [9,10,15,27]. Therefore, we speculated that short-term of empagli ozin treatment was not enough to play an anti-in ammation effect.…”
Section: Discussionmentioning
confidence: 72%
“…In recent years, some mechanisms underlying the bene cial effect of SGLT2 inhibitor on cardiovascular diseases have been proposed. The decreased toxicity of glucose to endothelial cells may be a potential mechanism in preventing diabetic ApoE-/-mice atherosclerosis [27]. And dapagli ozin could improve the differentiation of epicardial adipose tissue and perivascular adipose tissue [28].…”
Section: Discussionmentioning
confidence: 99%
“…The duration in the experiment was 12 weeks, and the experimental group was treated with SGLT2i beginning at the 7th week. Combining previous studies, SGLT2i may inhibit inflammatory mediators with a duration of at least 8 weeks [8,9,44,49]. Therefore, short-term empagliflozin treatment may not be enough to have an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 93%
“…In diabetic states, SGLT2 inhibitions might enhance glycemic control and lipoprotein clearance [21] while lowering sympathetic activation [50]. The decreased toxicity of glucose to endothelial cells may be a potential mechanism involved in the prevention of atherosclerosis in diabetic ApoE-/-mice [49]. While in non-diabetic conditions, SGLT2 inhibitors could increase adiponectin levels and reduce fat deposition [20].…”
Section: Discussionmentioning
confidence: 99%